Photocatalytic Oxidation of Diethyl Sulfide Vapor over TiO2-Based Composite Photocatalysts - Dmitry Selishchev (Molecules, 2014)
Composite TiO2/activated carbon (TiO2/AC) and TiO2/SiO2 photocatalysts with TiO2 contents in the 10 to 80 wt. % range were synthesized by the TiOSO4 thermal hydrolysis method and characterized by AES, BET, X-ray diffraction and FT-IR ATR methods. All TiO2 samples were in the anatase form, with a primary crystallite size of about 11 nm. The photocatalytic activities of the TiO2/AC and TiO2/SiO2 samples were tested in the gas-phase photocatalytic oxidation (PCO) reaction of diethyl sulfide (DES) vapor in a static reactor by the FT-IR in situ method. Acetaldehyde, formic acid, ethylene and SO2 were registered as the intermediate products which finally were completely oxidized to the final oxidation products – H2O, CO2, CO and SO42− ions. The influence of the support on the kinetics of DES PCO and on the TiO2/AC and TiO2/SiO2 samples’ stability during three long-term DES PCO cycles was investigated. The highest PCO rate was observed for TiO2/SiO2 photocatalysts. To evaluate the activity of photocatalysts the turnover frequency values (TOF) were calculated for three photocatalysts (TiO2, TiO2/AC and TiO2/SiO2) for the same amount of mineralized DES. It was demonstrated that the TOF value for composite TiO2/SiO2 photocatalysts was 3.5 times higher than for pure TiO2.